Architecture of Memory: Knowledge and Development Approaches - Sitienei, Emily C.; Nyabuto, Esther (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
This chapter outlines the nature of memory, memory systems, and types of memory. Memory is a complex of encoding, storing, and retrieving information. This study uses different kinds of memory for information such as personal experiences, specific skills, and abstract concepts. Classification of memory is based on the length of time in which the information is held. Sensory memories hold a large amount of ‘raw’ sensory information for a very short time. Short-term memory systems hold a small amount of information for a very short time, while long-term memory systems hold a large amount of information for an indefinite period. Without the encoding cues, information in long-term memory will be hard to retrieve. Retrieval of information from long-term memory will also depend on the availability and accessibility of items in long-term memory. This chapter on the architecture of memory is applicable in any learning institution since learners need to understand the way their memory operates.